High-zinc rice as a breakthrough for high nutritional rice breeding program - Barokah, U.; Susanto, U.; Swamy, M.; Djoar, D.W.; Parjanto (IOP Publishing, 2018)
WHO reported climate change already takes 150,000 casualties annually, due to the emergence of various diseases and malnutrition caused by food shortages and disasters. Rice is the staple food for almost all of Indonesian citizens, therefore Zn biofortification on rice is expected to be effective, efficient, massive, and sustainable to overcome the Zn nutritional deficiency. This study aims to identify rice with high Zn content and yield for further effort in releasing this variety. Ten lines along with two varieties as a comparison (Ciherang and Inpari 5 Merawu) were tested in Plumbon Village, Mojolaban Subdistrict, Sukoharjo Regency during February-May 2017. The experiment was designed in a Randomized Completely Block Design with four replications on a 4 m x 5 m area, with 25 cm x 25 cm plant spacing using seedling transplanting techniques of 21 days old seeds. The results showed that the plant genotypes treated had differences in yield characteristics, heading date, harvest age, panicle number, filled and un-filled grain per panicle, seed set, 1000 grains weight, Zn and Iron (Fe) content in rice grain. B13884-MR-29-1-1 line (30.94 ppm Zn, 15.84 ppm Fe, 4.11 ton/ha yield) and IR 97477- 115-1-CRB-0-SKI-1-SKI-0-2 (29.61 ppm Zn, 13.49 ppm Zn, 4.4 ton/ha yield) are prospective variety to be released. Ciherang had Zn content of 23.04 ppm, 11.93 ppm Fe, and yield of 4.07 t/ha.